A study on nuclear analysis of the divertor region of the CFETR. (13th October 2021) - SAIDAHMED, Rayyan; YAO 姚, Damao 达毛; WU 伍, Qiuran 秋染; LIU 刘, Songlin 松林; XU 许, Tiejun 铁军
Abstract: This paper presents the nuclear analysis performance of the Chinese Fusion Engineering Test Reactor (CFETR) divertor region using the MCNP-5 Monte Carlo N-particles code in a 3D geometry model. We assessed the nuclear responses of the divertor region component systems and evaluated their shielding capability, which can support the development strategy of the physical and engineering design of the CFETR. Model specification based on the latest CAD model of the CFETR divertor has been integrated into the CFETR MCNP reference model with a major/minor radius R  = 7.2 m/ a  = 2.2 m in the 22.5° model, and a fusion-power range of around 1–1.5 GW. The nuclear heating and radiation damage of the divertor system are enhanced compared to that of the ITER and the earlier CFETR design. The initial nuclear responses of the toroidal field coil and vacuum vessel systems showed that the shielding of the current divertor design is not sufficient and optimization work has been carried out. We also carried out calculations and analysis using a hypothetical operating scenario of over 14 years. An excellent improvement in the nuclear performance has been obtained by the improved additional shielding block in the divertor region when referring to the ITER design limit, which can support the design of the future update of the divertor region systems of the CFETR.